Improved detection sensitivity for heavy trace elements using a miniature laser ablation ionisation mass spectrometer. Issue 11 (7th September 2017) - Wiesendanger, R.; Tulej, M.; Riedo, A.; Frey, S.; Shea, H.; Wurz, P.
Abstract : Detecting heavy trace elements with a miniature laser spectrometer on a lunar meteorite. Abstract : Laser ablation ionisation time-of-flight mass spectrometry is a versatile technique to obtain highly sensitive measurement of the elements and isotope composition of solid materials. Because of the measurements of nearly all elements in the sample, large ion rates of abundant elements may reduce the detection efficiency for heavier elements arriving later at the detector system. If this occurs, it will affect the capability of quantitative measurements of heavy species. We demonstrate that by implementation of a short high-voltage (HV) pulse, we can remove the high rate ions that reduce the detection efficiency of the ion detector to measure trace elements, which otherwise would not be detectable. The location of a suitable electrode in the given ion optical system, the timing and the pulse shape were determined with the help of numerical ion trajectory simulations using the SIMION software. An HV pulse removes ions of lighter elements, including Na, K, and Mg from the analysed ion beam, which are typically the most abundant species in rocks and soils, allowing sensitive analysis of heavy trace elements. Using standard NIST reference materials we determined detection limits in the sub-ppm range and accomplished isotope ratio measurements of Pb with an accuracy in the per mill range. Further investigations of trace elements of the KREEP material in a lunar sample demonstrate that the miniature LIMS system can be used for in situ analysis of rocks and soils, and for investigations of geological processes and dating.